Avaliação da qualidade de vida de pessoas com esquistossomose hepatoesplênica e mielorradiculopatia esquistossomótica - Silvania Junia Roriz (2015)
Schistosomiasis mansoni is a debilitating parasitic disease highly prevalent in tropical and subtropical regions of the world. It is considered a serious public health problem because of its high morbidity rate. In the literature, there is scare information on schistosomiasis to identify, map and quantify the impact of this disease. The objective of this study was to assess quality of life related to health of patients with mansonic hepatosplenic shistosomiasis and schistosomal myeloradiculopathy, its association with the main manifestations of the disease and the existence of functional impairment for the individuals affected. Volunteers were admitted at the clinic of infectious and parasitic diseases of the Hospital das Clínicas/UFMG (CTR/Orestes Diniz) from July to October 2014. We interviewed 97 people: 49 with hepatosplenic schistosomiasis, 22 with schistosomal myeloradiculopathy and 26 without schistosomiasis (control group). All participants completed the questionnaire on quality of life, WHOQOL-Bref, and the questionnaire to evaluate the functional performance, Human Activity Profile (HAP). Data were stored in the software Statistical Package for Social Sciences 20.0 (SPSS, IBM Company, Chicago, IL). Patients with hepatosplenic schistosomiasis and shistosomal myeloradiculopathy had lower scores of quality of life compared to control group. The analysis by domains of the WHOQOL-Bref not showed statistically significant difference, as well as in the evaluation of functional performance. In conclusion, lower quality of life is more evident in schistosomiasis mansoni than the quality of life of uninfected. The disease did not alter functional performance. Other associated diseases (hypertension, diabetes mellitus, thyroid disease and others) also did not change the quality of life of people with schistosomiasis.